An Econometric Modelling of Absorptive Capacity, Credit Market Development and Economic Development in Nigeria (Global Journal of Human-Social Science, 2012)
This paper empirically examines the relationship between absorptive capacity, credit market development and economic development in Nigeria. Recent theoretical works show the significance of absorptive capacity and credit market development to economic growth. In this study, the perceived relationship between absorptive capacity, credit market development and economic growth is estimated econometrically using the Ordinary Least Square Estimation Method (OLSEM). The result showed that there is a substantial positive effect of the selected macroeconomic variables on economic growth in Nigeria. The Granger causality test showed that absorptive capacity, human capacity development, lending rate, savings, gross domestic investment and gross domestic product indicates an evidence of causality from the selected macroeconomic variables (ABC, HCD, LR, SAV and GDI) to economic growth/development.
Keywords: Economic growth; credit market; economic development; absorptive capacity; and microeconomic policy